Pelatihan Pembuatan Media Promosi Berbasis Multimedia Pada Sekolah Dasar - Purba, Bister; Purwa Hasan Putra; Oktavia Ully Artha Silalahi; Yulia Agustina Dalimunthe; Wiwin Sry Adinda Banjarnahor (Forum Kerjasama Pendidikan Tinggi, 2024)
This training was carried out as part of a community service program, with the aim of empowering educators and teachers at SDS Bina Satria Mulia through improving skills in making multimedia-based promotional media. At SDS Bina Satria Mulia, the process of making multimedia-based promotional media often faces various obstacles. Among them are the limited number of educators who are skilled in the field of multimedia and the lack of adequate technical knowledge and skills in the use of multimedia software. This certainly results in ineffective promotional content. The design is less attractive so that the resulting promotional media may appear unprofessional and less attractive. In addition, limited knowledge of multimedia software and tools results in non-optimal use, resulting in low quality content for promotional media. The lack of knowledge about multimedia also hinders the ability to create innovative and interesting content so that the resulting promotional media tends to be monotonous and the inability to keep up with the latest trends in design and digital technology makes promotions outdated. So with the problems that occur, it is necessary to hold a Multimedia-Based Promotional Media Creation Training at SDS Bina Satria Mulia to enable teachers and educators to produce more attractive and professional promotional materials, such as digital brochures, school profile videos, and social media posts and gain technical skills in the use of graphic design software, video editing, and other multimedia tools. The level of understanding of the making of multimedia-based promotional media from 20 participants showed that the level of understanding of the training participants before the training on making multimedia-based promotional media with 15 people did not understand, 3 people understood a little, 1 person understood enough and only 1 person understood. After participating in the training, the level of understanding was quite understood by 2 people, understood by 4 people and understood by 14 people. So, it can be concluded that before the training the percentage of people who did not understand about promotional media was 75% and after attending the training the percentage increased by 70% for the level of understanding of making promotional media.